Comparison of the Effect of High Impact Aerobic Dance Exercise Versus Zumba on Increasing Maximum Oxygen Volume in Adolescent Women - Puspodari, Puspodari; Setijono, Hari; Wiriawan, Oce; Arfanda, Poppy Elisano; Raharjo, Slamet; Muharram, Nur Ahmad; Himawanto, Wasis; Allsabah, M. Akbar Husein; Koestanto, Susilaturochman Hendrawan (Physical Education Theory and Methodology, 2022)
The study purpose was to compare high impact aerobic dance exercise versus Zumba to increase Maximum Oxygen Volume (VO2max) in adolescent women. Materials and methods. This research is quasi-experimental with a two-group pretest-posttest design research design. A total of 30 adolescent women from the Student Activity Unit (UKM) aerobic gymnastics at Universitas Nusantara PGRI Kediri, aged 18-24 years, body mass index (BMI) 18.5-24.9 kg/m2, normal blood pressure participated in the study. Respondents were randomly divided into two groups, namely ZADE (n = 15, Zumba aerobic dance exercise) and HADE (n = 15, High impact aerobic dance exercise). HADE and ZADE were conducted for 30 minutes/session, with an intensity of ≥ 85% HRmax, as often as 3 times/week, and both types of training were performed for 8 weeks. Measurements of VO2max, oxygen saturation (SpO2), and heart rate at rest (HRrest) were pre-test and 1×24 hours post-test after 8 weeks of training intervention. Statistical analysis used Paired Sample T-Test with a significance level of 5%. Results. Paired Sample T-Test results showed significant differences in average VO2max, SpO2, HRrest between pretest vs. posttest in both groups (p ≤ 0.001). Conclusions. Based on the study results, we have concluded that both HADE and ZADE increase VO2max, SpO2, and decrease HRrest. But HADE is more effective in increasing VO2max, SpO2, and lowering HRrest than ZADE in adolescent women.